Impact of Singapore’s ageing population on the macroeconomy. - Park, Sun Jung. (2010)
This paper discusses the macroeconomic implications of a rapid ageing population in Singapore. Not only is the rapidly graying population expected to decrease savings and investments, it is also expected to increase government expenditure. In addition, the shrinkage of labour supply implies lower tax revenue, resulting in possible government debt. An ageing population has severe implications on labour productivity which could in turn affect the competitiveness of the economy. Furthermore, the reduction in mandatory savings also makes exchange rate management difficult in Singapore. This is because the savings in the Central Provident Fund and budget surplus accrued over the years allow the Monetary Authority of Singapore to control the nation’s inflation through re-injection of liquidity into the economy. Therefore, the authority might lose an effective inflation management tool. Our findings show that an ageing population will also affect the current account due to the fall in savings. It is thus vital for the government to determine how an ageing population will affect the economy and make appropriate plans for these upcoming challenges. Finally, we suggest several ways that the government could consider to help alleviate the problem of ageing on the macroeconomy.